EXPLORING LINGUISTICS IDENTITY FROM BRUNEI TO MEDAN: AN AUTOETHNOGRAPHY VIEW - N. Aini Hasyim Munthe Borneo; Sholihatul Hamidah Daulay (JALC : JOURNAL OF APPLIED LINGUISTIC AND STUDIES OF CULTURAL, 2026)
This study uses an autoethnographic approach to investigate the role that language plays in the formation of linguistic identity between Brunei Darussalam and Medan, Indonesia. It investigates how speakers adjust across multilingual and cultural borders, drawing on Decolonial Linguistics (Kelley, 2020) and Linguistic Identity Theory (Pavlenko & Norton, 2020). Self-interview data from a qualitative introspective case study highlight significant variations in pragmatics (kita, jua), pronunciation (A/E sounds), and vocabulary (kereta, lalu). Although these differences first led to misunderstanding, they eventually promoted linguistic awareness and identity negotiation. The results demonstrate that the speaker preserved cultural roots while creating a hybrid language identity that combined aspects of Indonesian and Bruneian. The research emphasizes autoethnography as an introspective method for comprehending the intersections of language, power, and belonging in Southeast Asia.